Witchshadow - Dennard, Susan (Dennard, Susan. Witchlands novel., 2021)
After Iseult's reunion with her heartstister Safi she flees Cartorra to summon dangerous magic while the Bloodwitch Aeduan is beset by forces he cannot understand and villains from legend reawaken across the Witchlands.